Aktual'noe interv'iu . Aktual'noe interv'iu . Relevant Interview . Актуальное интервью - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with Anatoli Chubais on privatization and his disagreements with Vice President Alexandr Rutskoi. Featured in the program: Chubais, Anatolii Borisovich (Deputy Prime Minister of the Government of the Russian Federation) Интервью с Анатолием Чубайсом о приватизации и разногласиях с вице-президентом Александром Руцким. В программе участвуют: Чубайс, Анатолий Борисович (Заместитель председателя правительства Российской Федерации)